2020
DOI: 10.17765/2176-9206.2020v13n4p871-877
|View full text |Cite
|
Sign up to set email alerts
|

Análise epidemiológica de casos novos de hanseníase em uma antiga colônia do Estado de Minas Gerais (2000-2016)

Abstract: O objetivo desta pesquisa foi descrever e relacionar classificação operacional, vacinação com BCG e gênero entre casos novos de hanseníase na Colônia Padre Damião, município de Ubá, Minas Gerais, de 2000 a 2016. Os dados foram coletados a partir de fichas de notificação e entrevistas, totalizando 43 casos novos pesquisados. Gênero feminino, forma multibacilar e vacinados predominaram na análise descritiva. Além disso, observou-se diminuição na porcentagem de casos multibacilares em indivíduos com uma ou duas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…A higher percentage of individuals in the control group had a BCG vaccination scar (64.17%), which suggests that immunization for BCG is protective against leprosy. Corroborating the present study, other studies that analyzed the vaccination status of (non-ill) household contacts of patients with leprosy have reported that 60-67.85% of the non-ill respondents had a BCG vaccination scar (MENDONÇA et al, 2019;GARCIA et al, 2020), while the absence of a BCG vaccination scar is reported as a risk factor (SCHNEIDER; FREITAS, 2018).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…A higher percentage of individuals in the control group had a BCG vaccination scar (64.17%), which suggests that immunization for BCG is protective against leprosy. Corroborating the present study, other studies that analyzed the vaccination status of (non-ill) household contacts of patients with leprosy have reported that 60-67.85% of the non-ill respondents had a BCG vaccination scar (MENDONÇA et al, 2019;GARCIA et al, 2020), while the absence of a BCG vaccination scar is reported as a risk factor (SCHNEIDER; FREITAS, 2018).…”
Section: Resultssupporting
confidence: 76%
“…Most of the participants immunized with BCG had only one vaccination scar (96.15%). The presence of a single scar is the most frequent finding in studies conducted in Brazil, with a low frequency of leprosy in individuals with two scars (LAGES, 2017;LOZANO et al, 2019;GARCIA et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…15 Garcia et al (2020) Foi identificado neste estudo que a vacina BCG tem papel fundamental na prevenção da hanseníase, sendo a primeira dose fundamental para prevenir os casos multibacilares em mulheres e a segunda dose a forma clínica da doença em homens.…”
Section: Resultsunclassified
“…As evidências trazidas pelo estudo 15 são importantíssimas e passíveis de disseminação. Trata-se da relação da vacina BCG com a prevenção da hanseníase (Garcia et al, 2020), uma doença cuja o diagnóstico precoce favorece a minimização dos agravos, a prevenção através da vacina cientificamente atestada é uma ferramenta cujo uso é necessário e as consequências positivas indubitavelmente reais.…”
Section: Resultsunclassified
See 1 more Smart Citation